Brazil : Eradicating Child Labor in Brazil - World Bank (Washington, DC, 2013)
The report reviews evidence of child labor in Brazil, and the Government's efforts to eradicate its worst forms, by examining background assessments of ongoing programs for its prevention. It seeks to identify promising strategies, addressing the needs of highly vulnerable children in urban areas, engaged in activities such as drug commerce, prostitution, or other dangerous activities. One such program is the Child Labor Eradication Program - PETI - unique in that it provides a conceivable strategy to address by 2002, the incidence of child labor. The assessments demonstrate that the program has been successful in reducing child labor rates, school attendance has increased as a result of the program, and, attitudinal and other changes have occurred as a result of the program. The report outlines the political, and legal debate on child labor, examining indicators and trends in Brazil, as well as the determinants of child labor, linking child labor and poverty to its structural determinants, and how economic crises affect child labor. A description of child labor outcomes follows, specifying how child labor leads to low educational attainment, and low earnings, including its implications for adult wages, income, and poverty, summarizing targeted program expansion and future challenges.